The effects of hydrogen peroxide on plant growth, mineral accumulation, as well as biological and chemical properties of Ficus deltoidea - Nik Muhammad Nasir, Nik Nurnaeimah; Mat, Nashriyah; Mohd, Khamsah Suryati; Badaluddin, Noor Afiza; Yusoff, Nornasuha; Sajili, Mohammad Hailmi; Mahmud, Khairil; Mohd Adnan, Ahmad Faris; Khandaker, Mohammad Moneruzzaman (MDPI, 2020)
Hydrogen peroxide (H2O2) is defined as a reactive oxygen species (ROS), able to cause damage to a variety of cellular structures. On the other hand, recent work has demonstrated that H2O2 can also act as a potent signaling molecule that mediates various physiological and biochemical processes in plants. This study was carried out to investigate the effects of H2O2 on the growth, mineral nutrient accumulation, as well as the biologic and chemical properties of Ficus deltoidea var. deltoidea. F. deltoidea plants were spray-treated with 0- (control), 8-, 16-, 30- and 60-mM H2O2 under field conditions. Plant height, leaf area, chlorophyll content, net photosynthetic rate, stomatal conductance and quantum yield of the F. deltoidea plants significantly increased after treatment with 16 and 30-mM H2O2. The results indicate that 60-mM H2O2 increased the accumulation of arsenic, iron and sodium content in the leaves of F. deltoidea. On the other hand, 8-mM H2O2 significantly enhanced the accumulation of arsenic, iron, calcium and potassium content in the syconium of F. deltoidea plants. In addition, H2O2 treatment did not produce any significant effects on antimony and magnesium accumulation in the leaves or the syconium of F. deltoidea plants. The results show that the F. deltoidea plant has strong antidiabetic properties and its α-glucosidase activity increased in treated plants compared to standard acarbose. Hydrogen peroxide, particularly in concentrations of 16 and 30 mM, increased the antioxidant activity, total phenolic and flavonoid content and the vitexin and isovitexin content. There was a positive correlation between antioxidant activity with total phenol and total flavonoid content in H2O2-treated plants. The quantitative analysis by HPTLC indicates that the amount of vitexin and isovitexin increased with the higher concentrations of H2O2. From this study, it can be concluded that spraying 16 and 30-mM H2O2 once a week enhances growth, mineral accumulation and stimulates bioactive compounds of the F. deltoidea plants.